Adoption of Foreign Technologies in Korean Manufacturing Firms: Characteristics and Microfoundations - 서중해 (14255, 2015)
The primary goal of this paper is to explore the microeconomic foundation of Korean firms’ adoption of foreign technologies. The paper also reviews the overall trend of international technology transfers to Korea. The period covered in this paper is Kore